Kewenangan Perorangan Dalam Menguasai Tanah Pesisir - Fransisca Jallie Pattiruhu (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2024)
Land issues certainly never end and still occur frequently. This research was conducted on the basis that there are still many people who question the status of ownership rights to land in coastal areas. As in Article 9 paragraph 2 of the UUPA, it is the basis of legitimacy for every Indonesian citizen, both men and women, to have the same opportunity to obtain rights to land and obtain benefits from that land. So of course everyone has the right to control land in coastal areas, but what is the status of their authority? The research method used is legal research, with using a statutory approach and a conceptual approach related to the authority to control individuals over land in coastal areas. The conclusion from the results of the analysis carried out can be understood that property rights cannot be used as a basis for individual rights to coastal land because coastal land is land located in coastal areas, which means that coastal areas are potential areas and are the authority of both district/city governments.